(untitled) (Estudios Gerenciales, 2016)
The learning capacity of social based Mexican micro-entrepreneurs to generate new knowledge and incorporate it to its products and services is evaluated. The above is done through a confirmatory factor analysis and structural linear equation system, and the presence of static and dynamic dimensions in learning capacity, which are represented by individual stocks and flows of knowledge. The positive relationship between them demonstrates the presence of learning processes that impact positively their economic performance.